2021
DOI: 10.2147/ijgm.s316297
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Limb Artery Indices and Endothelial Functional Tests for the Degree of Coronary Artery Stenosis in a Diabetic Population

Abstract: Objective To investigate the correlation between limb artery indices (brachial-ankle pulse wave velocity and ankle-brachial index), endothelial function index (FMD value), and the degree of coronary artery stenosis in diabetic patients and analyze their values in predicting the degree of coronary artery stenosis. Methods The study included 151 patients with type 2 diabetes mellitus and suspected coronary atherosclerotic heart disease. The patients were divided into “cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In our study, the analysis of 1752 EH patients found that FMD was an independent predictive factor for CAD in EH patients; compared with EH patients with FMD > 7.1%, FMD ≤ 7.1% could increase the weight of 100 points in the nomogram and contributed the most to CAD risk. Wang et al [ 26 ] also found similar results through the study of 151 diabetic patients; FMD was independently associated with CAD, and could predict the degree of coronary artery stenosis alone or in combination with ankle brachial index. At present, the cut-off value of endothelial dysfunction defined by FMD is controversial.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, the analysis of 1752 EH patients found that FMD was an independent predictive factor for CAD in EH patients; compared with EH patients with FMD > 7.1%, FMD ≤ 7.1% could increase the weight of 100 points in the nomogram and contributed the most to CAD risk. Wang et al [ 26 ] also found similar results through the study of 151 diabetic patients; FMD was independently associated with CAD, and could predict the degree of coronary artery stenosis alone or in combination with ankle brachial index. At present, the cut-off value of endothelial dysfunction defined by FMD is controversial.…”
Section: Discussionmentioning
confidence: 59%
“…This study found that smokers with EH were 1.47 times more likely to develop CAD than non-smokers, suggesting that quitting smoking is of great significance for the prevention and treatment of CAD. Abdominal obesity and diabetes mellitus are related to metabolic diseases [ 18 ], and also act as important risk factors for ASCVD [ 26 ]. Our result demonstrated that for EH patients, CAD risk increased by nearly 20% for every 10 cm increase in waist circumference, and EH patients were 2.31 times more likely to develop CAD than those without diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%